Tourism development: An empirical study on Malaysia - Harun, Azhar (2013)
The study shows the government expenditure on the tourist sector (ExqM) and the cost of living in Malaysia (CosM) have a major influence to the increase of tourists in Malaysia (TouM).In actuality, there are many factors that have contributed to the progress of the tourism sector's income; however the study shows that the total number of hotels in Malaysia (Ho) and the increasing number of tourists to Malaysia (TouM) are the two main factors that boasted the tourism sector's income (ImT).With regards 10 the last equation, the output of the study shows, the initial period the tourism sector only plays a minor role in the country's GDP.However, under the present development policy, greater emphasis has been given to the development of tourist sector with the injection of more allocation under the new budget; it is expected that this sector is going to be one of the major earner and contributor to the GDP of Malaysia.Aside from that, this study also noted, with the influx of more tourists into Malaysia, the country will have to face with more cultural and social problems.